Prof. Zapukhlyak R.I. celebrate 50 anniversary - PCSS, Editorial_Team (Physics and Chemistry of Solid State, 2024)
Zapukhlyak Ruslan Ihorovych Vice-rector of Vasyl Stefanyk Prekarpathian National University, PhD in physical and mathematical sciences, Professor, Member of the organizing committee of International Freik Conferences on Physics and Technology of Thin Films and Nanosystems